A MORE SINISTER CAUSE OF LOWER BACK PAIN IN THE THIRD TRIMESTER: A CASE REPORT OF PREGNANCY AND LACTATION-ASSOCIATED OSTEOPOROSIS - Hua, Goh Hui; Azman, Siti Sanaa Wan; Ali, Masliza Hanuni Mohd; Kamudin, Nur Azree Ferdaus Bin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Pregnancy and lactation-associated osteoporosis (PLO) is a rare but painful condition that tends to occur during the third trimester or postpartum period, with an incidence of 0.4 cases/100,000 women and 70% of those affected are primiparous. The main symptom is severe lower back pain as this condition often causes vertebral fractures which can be multiple. CASE We present a case of a 28-year-old female with an underlying right coronary artery fistula and endometriosis. She is para 1 and delivered her child in December 2022. During this pregnancy, she had a history of severe back pain during the third trimester. There was no history of falls or any neurological deficits. She gave a history of coccyx fracture following a fall eight years ago but recovered uneventfully. She breastfed her baby for five months post-partum and her back pain persisted during this period which prompted further investigations for her. She did not consume any steroids and there were no signs and symptoms to suggest Cushing’s Syndrome. Initial biochemical results were all within normal range: calcium 2.41 mmol/L, phosphate 1.0 mmol/L, ALP 84 U/L, TSH 1.83 m IU/L, FT4 14.8 pmol/L and i-PTH 4.8 pmol/L. Overnight dexamethasone suppression test was appropriately suppressed (15 nmol/L). Her vitamin D level was insufficient at 51 nmol/L. Radiography confirmed T10 vertebral compression fracture and her DEXA scan revealed that she is osteoporotic with spine Z-score -3.2, and femur Z-score -3.5. She was managed with oral cholecalciferol 1000 units daily and calcium carbonate 500 mg twice daily as she preferred to not use any anti-resorptive agent. Her back pain improved after cessation of lactation and with analgesics. CONCLUSION PLO is a rare condition and should be suspected in pregnant women who complain of back pain to ensure early diagnosis and intervention. Secondary causes of osteoporosis need to be ruled out as well.